Corneal Transplantation - Vajpayee, Rasik (Panamá : Jaypee-Highlights, 2002)
El libro señala que la querotosplastia es considerada como un frecuente desempeño que se realiza a nivel del ojo
Secction 1 Historical aspects, preoperative considerations and eye banking Section II Penetrating Kerotoplasty Section III Penetrating Kerotoplasty: managment of complications Section IV Lamellar kerotoplasty an d other
Incluye indice
Keywords: CORNEA; QUERATOPLASTÍA